VEDANADHYAYA - A CLINICAL APPROACH TO PEDIATRIC EXAMINATION IN KASHYAPA SAMHITA (International Journal of Ayurveda and Pharma Research, 2018)
Kashyapa Samhita is a book of pediatrics having main focus on the health and well-being of children and their pathological manifestations. The most revered source book available on Kaumarbhritya, is presented in the form of compilations of the preaching of Acharya Kashyapa by his disciple Vridhha Jivaka. The Kashyapa samhita available today is actually one fourth or even less than what it would have been in its original form. Fortunately we have Vedanadhyaya where in 32 pediatric illnesses are described. The text is divided in various sections (Sthanas) of which Vedanadhyaya is twenty fifth chapters in Sutra Sthana. Acharya Kashyapa has provided us a strong diagnostic tool which is useful in day to day practice of pediatrics. He undoubtedly laid the foundation stone of clinical pediatrics. Vedanadhyaya concerns the symptomalogy of various diseases in children and serves as a great guidance for pediatric examination and diagnosis as children are unable to narrate their symptoms themselves. So the present article reviews the original text of the chapter and critically analyses it in light of contemporary medical science.